Englishs Gulch flows past meadows on the way to the River - Branch Cultural Historical Association (2008)
Two Gulches adjacent to the Flats on the east side of the River provide valuable farming land as well as great places for the nature lover to explore. Englishs Gulch, the gulch closer to the ocean, was one of the tracts of land cleared in Branch in the 1800s as the population grew and new families required land for vegetable gardens and livestock pasturage. Prior to the Englishs arrival in Branch, this gulch was known as Cottlers Gulch. Cottler was the captain of a schooner from Placentia forced to over-winter in Branch before the community was settled. Poor weather prevented the boat from getting out the Gut, forcing the crew to stay until the ice broke up in the spring. While details about their stay are scanty, it is said they used provisions from the boat to get through the winter and they may have built a log cabin.